Coronin 2B regulates dendrite outgrowth by modulating actin dynamics. Issue 18 (31st July 2020) - Chen, Yuewen; Xu, Jinying; Zhang, Yulin; Ma, Shuangshuang; Yi, Wanying; Liu, Saijuan; Yu, Xiaojun; Wang, Jiali; Chen, Yu
Abstract : Cytoskeletal remodeling is indispensable for the development and maintenance of neuronal structures and functions. However, the molecular machinery that controls the balance between actin polymerization and depolymerization during these processes is incompletely understood. Here, we report that coronin 2B, a conserved actin‐binding protein, is concentrated at the tips of developing dendrites and that knockdown of coronin 2B inhibits the growth of dendrites. Importantly, coronin 2B interacts with actin and reduces the F‐actin/G‐actin ratio. Furthermore, the coiled‐coil domain of coronin 2B is required for its oligomerization, thus confining coronin 2B to neurite tips. Our findings collectively suggest that coronin 2B is important for promoting dendrite outgrowth by limiting the speed of actin polymerization at growth cones.